N‐Ethyl‐N‐nitrosourea mutagenesis in the mouse provides strong genetic and in vivo evidence for the role of the Caspase Recruitment Domain (CARD) of CARD‐MAGUK1 in T regulatory cell development. Issue 3 (March 2014) - Salisbury, Emma M.; Wang, Lihui; Choi, Onjee; Rutschmann, Sophie; Ashton‐Rickardt, Philip G.
Summary Natural regulatory T (nTreg) cells generated in the thymus are essential throughout life for the maintenance of T‐cell homeostasis and the prevention of autoimmunity. T‐cell receptor (TCR)/CD28‐mediated activation of nuclear factor‐κB and (J)un (N)‐terminal kinase pathways is known to play a key role in nTreg cell development but many of the predicted molecular interactions are based on extrapolations from non‐Treg cell TCR stimulation with non‐physiological ligands. For the first time, we provide strong genetic evidence of a scaffold function for the Caspase Recruitment Domain (CARD) of the TCR signalling protein CARD‐MAGUK1 (CARMA1) in nTreg cell development in vivo. We report two, new, N‐ethyl‐N‐nitrosourea‐derived mutant mice, Vulpo and Zerda, with a profound block in the development of nTreg cells in the thymus as well as impaired inducible Treg cell differentiation in the periphery. Despite independent heritage, both mutants harbour different point mutations in the CARD of the CARMA1 protein. Mutations in vulpo and zerda do not affect expression levels of CARMA1 but still impair signalling through the TCR due to defective downstream Bcl‐10 recruitment by the mutated CARD of CARMA1. Phenotypic differences observed between Vulpo and Zerda mutants suggest a role for the CARD of CARMA1 independent of Bcl‐10 activation of downstream pathways. We conclude that our forward genetic approach demonstrates a critical role for the CARD function of CARMA1 in Treg cell development in vivo.